USING ORAI APPLICATION IN TEACHING PRONUNCIATION - Lilis Suryani; Trisnendri Syahrizal; Ula Nisa El Fauziah (University of Kuningan, 2019)
Teaching in 4.0 era cannot be separated with Information and Communication Technology (ICT). There are many applications that can be used in learning and teaching process. ORAI application is chosen to be used as teaching tool in learning pronunciation. The main objective of this research is to discover the pro and cons from students as the main user in using ORAI application in learning pronunciation. This research implemented qualitative as research method and the participants of the research was 35 students of third semester of English students in IKIP Siliwangi. The data were collected by observation and interview. The result of the research showed that most of the participants agree that ORAI brings more benefits in learning pronunciation practice class. Their agreement can be classified into four categories: accessibility, comfortability, technicality, and integrated learning. The students were motivated and they could learn effectively. While, some of the students indicated that they did not want to use this application, they just delivered that this application has weaknesses in their process of practicing English pronunciation. Their cons on the use of ORAI are classified into two categories; topic difficulties and technicalities. Overall, the implementation of ORAI has positive effect for students in pronouncing correctly and they have good feedback to trigger them for practicing a lot. On the other hand, pronouncing English well will make a big contribution to their communication skills.Â Â